Odpowiedź:
[tex]a_6 = \frac{1}{9} \\a_1q^5 = \frac{1}{9}[/tex]
[tex]a3 = -3\\a1q^2 = -3[/tex]
Otrzymujemy układ równań
[tex]\left \{ {{a_1q^5 = \frac{1}{9} } \atop {a_1q^2 = -3}} \right.[/tex]
Dzielimy stronami:
[tex]\frac{q^5}{q^2} = \frac{\frac{1}{9} }{-3} \\q^3 = -\frac{1}{27} \\q = -\frac{1}{3}[/tex]
Z drugiego równania:
[tex]a_1 = \frac{-3}{q^2} \\a_1 = \frac{-3}{\frac{1}{9} } = -3 * 9\\a_1 = -27[/tex]
Znając już [tex]a_1[/tex] oraz q możemy policzyć
[tex]a_7 = a_6q \\a_7 = \frac{1}{9} * -\frac{1}{3} = -\frac{1}{27}[/tex]
[tex]S_5 = -27 * \frac{1-(-\frac{1}{3} )^5}{1+\frac{1}{3} } = -27*\frac{1+\frac{1}{243} }{\frac{4}{3} } = -27*\frac{244}{243} * \frac{3}{4} = -\frac{61}{27} = -2 \frac{7}{27}[/tex]